ANESTHETIC CONCERNS IN PAEDS CARDIAC CATHETERIZATION AT ARMED FORCES INSTITUTE OF CARDIOLOGY / NATIONAL INSTITUTE OF HEART DISEASES - Amna, Dr; Niaz, Naila; Farid, Zainab; Younas, Umair; Javaid, Rehana (Pakistan Armed Forces Medical Journal, 2021)
Objective: To examine the types of procedures and analyze the frequency of anesthesia-related complications during pediatric cardiac catheterization.Study Design: A prospective observational study.Place and Duration of Study: Pediatric Cardiac Catheterization Lab at AFIC/NIHD Rawalpindi, from July 2019 to Nov 2019.Methodology: Total 180 consecutive patients undergoing cardiac catheterization fulfilling inclusion criteria were studied. Demographic variables, diseases, type of procedure, variables and anesthesia-related complications were noted. All the data was analyzed using SPSS-23.Results: The study included180 patients where 96 (53.3%) were male and 84 (46.7%) were female. Most of the patients in our study were between ages 1 to 3 years (85). 99 (55.0%) patients had diagnostic cardiac catheterizetion (CC), while 81 (45%) patients underwent interventional procedures. The overall complication rate noted as 18.9%, including arrhythmia in 11.1% followed by hypotension 4.4%, laryngospasm 3.9% and inotropic support requirement 3.3%, Mortality was 0.6%. Most of the patients presenting to the pediatric cardiac catheterization lab were for PDA device closure (16.6%). Age of child was found to be significant risk factor for cardiac catheterizetion associated complications with a p-value of 0.022.Conclusion: Congenital and structural heart disease catheterization procedures are progressively increasing, especially due to the medical advances and complex interventional therapeutic procedures. A thorough preanesthesia assessment should be carried out to optimize before cardiac catheterization.